URGENSI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS TEKNOLOGI INFORMASI - Asep Rahmatullah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Islamic Religious Education (IRE), as a cornerstone of character and moral development for students, faces complex challenges in the digital age, particularly regarding curriculum content, teaching methods, and assessment systems.This research employs a qualitative literature review to formulate an innovative, adaptive, and contextual learning model. The findings indicate that the integration of information technology through the use of digital media such as animated videos, learning management systems (LMS), and interactive platforms along with the application of constructivist approaches, blended learning models (such as the flipped classroom), and the TPACK (Technological Pedagogical Content Knowledge) framework can create learning that is more interactive, personalized, student-centered, and meaningful by shifting the assessment paradigm from merely cognitive to holistic through project-based assessment, portfolios, and observations to measure the internalization of values and spiritual-social applications. Thus, this design not only contributes theoretically to enriching the instructional repertoire of Islamic Education but also addresses the practical challenges of learning effectiveness and digital literacy ultimately serving as a strategic transformation to shape a generation of Muslims who are religious, of noble character, critical, and technologically competent, with the caveat that its success depends heavily on infrastructure readiness, improved teacher competence, and a balance ensuring that technology remains a means of instilling Islamic values, not an end in itself.